Optimalisasi Peran Kelompok Informasi Masyarakat (KIM) dalam Literasi Digital di Kabupaten Merauke - Jalal, Nur; Syahrabudin Husein Enala; Syahruddin (Papsel Journal of Humanities and Policy, 2025)
Kelompok Informasi Masyarakat (KIM) serve as strategic partners of the government in disseminating information to the public, particularly in remote and rural areas. In the era of digital transformation, the role of KIM is increasingly crucial in promoting digital literacy to enhance access, understanding, and utilization of information technology among communities. This study aims to examine and optimize the role of KIM in improving digital literacy in Merauke Regency. A qualitative approach was employed, using data collection techniques such as observation, in-depth interviews, and document analysis with several active KIM groups in Merauke. The results show that although KIM holds great potential as agents of digital literacy, limitations in human resource capacity, technological infrastructure, and lack of training are the main challenges. Therefore, optimizing the role of KIM requires regular training, cross-sector collaboration, and regulatory and budgetary support from the local government. Thus, KIM can become key drivers in building an inclusive and competitive digital society in Merauke.